Morphology of craters generated by hypervelocity impacts of micron‐sized polypyrrole‐coated olivine particles. (13th August 2014) - Li, Y. W.; Bugiel, S.; Trieloff, M.; Hillier, Jon K.; Postberg, F.; Price, M. C.; Shu, A.; Fiege, K.; Fielding, L. A.; Armes, S. P.; Wu, Y. Y.; Grün, E.; et al.
Abstract To understand the process of cosmic dust particle impacts and translate crater morphology on smoothed metallic surfaces to dust properties, correct calibration of the experimental impact data is needed. This article presents the results of studies of crater morphology generated by impacts using micron‐sized polypyrrole (PPy)‐coated olivine particles. The particles were accelerated by an electrostatic dust accelerator to high speeds before they impacted onto polished aluminum targets. The projectile diameter and velocity ranges were 0.3–1.2 μm and 3–7 km s−1. After impact, stereopair images of the craters were taken using scanning electron microscope and 3‐D reconstructions made to provide diameter and depth measurements. In this study, not just the dimensions of crater diameters and depths, but also the shape and dimensions of crater lips were analyzed. The craters created by the coated olivine projectiles are shown to have complicated shapes believed to be due to the nonspherical shape of the projectiles.